Identifikasi Faktor Penyebab Perceraian Sebagai Dasar Konsep Pendidikan Pranikah di Kabupaten Banyuwangi - Harjianto Harjianto; Roudhotul Jannah (Universitas Batanghari Jambi, 2019)
Divorcement rate in Banyuwangi district is the second rank in East Java province below Surabaya and third rank in national scale below Indramayu and Surabaya. In 2014, there are 7.106 cases that involve 6.798 couples. This research is aimed to identify the factors that cause divorce high rate in Banyuwangi district. This research uses a qualitative approach with a case study design that using a phenomenological perspective. Purposive sampling method was used and the samples in this research were 40 widows and widowers from 4 sub-districts in Banyuwangi with the highest divorce cases. Data was analyzed with qualitative descriptive analysis.The results shows that divorce was be caused by internal and external factors. Internal factors, namely economy (37,5 percent), responsibility (15 percent), and harmony (17,5 percent). Whereas external factors are infidelity (30 percent). The result of this study will be a recommendation in formulating a prenuptial education learning model based on family and school approaches in Banyuwangi district.